2013
DOI: 10.1111/jre.12120
|View full text |Cite
|
Sign up to set email alerts
|

Periostin increases migration and proliferation of human periodontal ligament fibroblasts challenged by tumor necrosis factor ‐α and Porphyromonas gingivalis lipopolysaccharides

Abstract: Periostin acts as an important modulator of hPDL cell-matrix dynamics. It modulates hPDL proliferation, migration and PI3K/AKT/mTOR pathway. It also helps in overcoming the altered biological phenotype that chronic exposure to periodontal pathogens and proinflammatory cytokines produce in hPDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…38,39 A former study reported that exogenous POSTN restores TNFα-suppressed migration of PDL cells. 36 These results indicated that suppression of PDL cell migration by TNFα may be caused by a decrease of POSTN. In the present study, we discovered that TNFα…”
Section: Discussionmentioning
confidence: 82%
“…38,39 A former study reported that exogenous POSTN restores TNFα-suppressed migration of PDL cells. 36 These results indicated that suppression of PDL cell migration by TNFα may be caused by a decrease of POSTN. In the present study, we discovered that TNFα…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we (16) and others (56,57) have shown that POSTN affects cell migration. In the current study, we show that cells expressing total POSTN exhibit heightened adhesion more than cells lacking POSTN or cells overexpressing isoform 1.…”
Section: Discussionmentioning
confidence: 83%
“…, Padial‐Molina et al. ) and induces migration and proliferation through the interaction with α v β 3 and α v β 5‐integrins (Li et al. , Utispan et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Padial‐Molina et al. ). Similar to other highly homologous proteins such as βigH3, periostin expression is regulated by TGF‐ß in response to mechanical stimulation (Rios et al.…”
mentioning
confidence: 99%